The Existence Of ATR/BPN in The Implementation of Electronic Certificates in the 3T Area Based on the Minister of ATR/BPN Regulation Number 3 Of 2023 - Syavira Azzahra; Temmy Fitriah Alfiany (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This research aims to examine the existence and role of the National Land Agency (BPN) in optimizing the implementation of Electronic Land Rights Certificates and the use of the Touch My Land application in the Outermost, Frontier, and Disadvantaged (3T) areas, especially in Sukabumi Regency, based on the Regulation of the Minister of ATR/BPN Number 3 of 2023 concerning Electronic Certificates. This study uses a normative and descriptive qualitative juridical approach by examining legal documents as well as the results of observations and interviews at the ATR/BPN Office of Sukabumi Regency. The results of the study show that BPN has strategic administrative authority in the land digitization process, but its implementation in the 3T area still faces various obstacles such as limited digital infrastructure, low community legal literacy, and not optimal policy socialization. From the perspective of state administrative law, the principles of rechtmatigheid and doelmatigheid have not been fully fulfilled, resulting in the lack of comprehensive legal certainty. Therefore, it is necessary to strengthen institutional capacity, as well as the integration of inclusive digital services to realize effective, efficient, and equitable land services in the 3T region. This study recommends reformulation of technical policies and acceleration of digitalization with a community participation-based approach.